Estrous cycle behaviour and reproductive pathology in an ageing female Malayan tapir (Tapirus indicus) in captivity at the Night Safari, Singapore. - Ng, Sin Hwee. (2013)
One of the main challenges in the captive breeding of solitary animals, such as the Malayan tapirs (Tapirus indicus), is the inappropriate introduction of breeding partners which could result in aggression and serious injuries. The possible behavioural cues of estrous in adult females have been investigated in previous studies. However, reproductive ageing or pathologies may cause such behavioural signs to be ambiguous, and mating opportunities could be adjourned due to low confidence in mixing the pair. This study investigates the estrous behaviour of an ageing female Malayan tapir, to facilitate the timely introduction of the female to a male Malayan tapir for captive breeding. Behavioural observations revealed only a slight increase in urine spraying, vocalisation and flehmen response during her estrous period. The focal female interacted more frequently with the male when she was in estrous but there were no observable signs of sexual attraction between the pair. Possible health conditions and reproductive pathologies related to ageing were evaluated and an age-related decrease in estradiol concentration seemed to be the likely cause of the lowered sexual drive and receptivity. Obesity was also suspected to have resulted in a decrease in estrous behaviour displayed by the focal female Malayan tapir.